2018
DOI: 10.1007/s10695-018-0495-z
|View full text |Cite
|
Sign up to set email alerts
|

Minimal water volume for intensively producing male Siamese fighting fish (Betta splendens Regan, 1910)

Abstract: Water volume is a key parameter affecting the individual rearing of male Siamese fighting fish (Betta splendens Regan, 1910). In this study, minimization of water volume was pursued by assessing growth, feed utilization, digestive enzyme activities, color coordinates, muscle quality, and carcass composition. One-month-old solid-red male fish (0.97 ± 0.01 g initial body weight) were distributed individually into glass aquaria with five alternative water volumes (100, 150, 200, 250, and 300 mL), comprising 15 fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
0
8
1
Order By: Relevance
“…Protein synthesis capacity and protein turnover rate were observed via RNA concentration and RNA/protein ratio. Low flesh RNA and RNA/protein ratio indicate a faster growth rate of the fish on comparing to a slower growth rate group [62]. However, in the current study, no significant effect on RNA, protein and RNA/ protein ratio in muscle were observed.…”
Section: Discussioncontrasting
confidence: 78%
“…Protein synthesis capacity and protein turnover rate were observed via RNA concentration and RNA/protein ratio. Low flesh RNA and RNA/protein ratio indicate a faster growth rate of the fish on comparing to a slower growth rate group [62]. However, in the current study, no significant effect on RNA, protein and RNA/ protein ratio in muscle were observed.…”
Section: Discussioncontrasting
confidence: 78%
“…No differences in growth performance and feed utilization were observed across the three dietary treatments, suggesting that all the fish have high ability to utilize the different preparations of mosquito larvae. The growth and feed utilization from the current study were relatively superior but within the ranges from aquaculture of this species (Mandal et al, ; Saekhow, Thongprajukaew, Phromkunthong, & Sae‐khoo, ; Sipaúba‐Tavares et al, ). Chai, Ji, Han, Dai, and Wang () reported increased VSI in fish fed with diets having optimized protein and lipid contents, relative to other less suitable diet formulations.…”
Section: Discussionmentioning
confidence: 48%
“…Significantly low flesh RNA and RNA/protein ratio indicates faster growing phase in a number of fish species (Saekhow, Thongprajukaew, Phromkunthong, & Sae‐khoo, ; Sunde et al, ; Thongprajukaew et al, ). Decreased RNA concentration (protein synthesis capacity) and RNA/protein ratio (protein turnover rate) while flesh protein concentration was improved, therefore suggests continuous growth of the fish reared against a black background, followed by the green and white respectively.…”
Section: Discussionmentioning
confidence: 99%